Analysis of Moderating Effect of Turnover Intention on the Relationship of Intrinsic Motivation and Employee Performance - Alsouri Al Ali, Amna Rashid Salim; Salahudin, Shahrul Nizam (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper presents an analysis of the moderating effect of turnover intention on the relationship between intrinsic motivation and the employee performance model. The moderation effect analysis was conducted using SmartPLS software version 3.0. The model was constructed within the software, and the analysis was conducted in two stages. The first stage involved a bootstrapping process to generate and determine the significance level and strength of the path. The second stage employed the PLS Algorithm process, generating a simple slope graph. Results from the bootstrapping process revealed a noticeable moderating effect attributed to turnover intention, supported by a t-statistics value of 2.514 and a statistically significant p-value of 0.006. Investigating the specifics of the path coefficient, the moderating impact on the relationship was quantified at -0.097, indicating a negative moderating influence. In practical terms, this suggests that turnover intention exerts a dampening effect on the connection between motivation and employee job performance. Regarding the simple slope analysis, it was found that the moderation effect of turnover intention on the relationship between intrinsic motivation and employee performance is particularly robust when turnover intention is lower. However, this effect diminishes to some extent when turnover intention is higher. These findings provide valuable insights into how the dynamics of these variables interact under varying levels of turnover intention.